Experimental effect of temperature and sedimentation on bleaching of the two Red Sea corals Stylophora pistillata and Acropora humilis - MOHAMMED S.A. AMMAR; AHMED H. OBUID-ALLAH; MONTASER A.M. AL-HAMMADY (Smujo International, 2013)
Abstract. Ammar MSA, Obuid-Allah AH, Al-Hammady MAM. 2013. Experimental effect of temperature and sedimentation on bleaching of the two Red Sea corals Stylophora pistillata and Acropora humilis. Nusantara Bioscience 5: 75-85. At 26°C (the control sample), the loss of zooxanthellae by each of the two studied corals Stylophora pistillata and Acropora humilis was very low. Cell viability of the two studied corals was similar at 26 and 29°C, but depicted a sharp decline of zooxanthellae lost at 31°C through time. As the temperature increased to 35°C, the loss of zooxanthellae from each host increased both with time and temperature elevation. The coral A. humilis had a higher decrease in its zooxanthellae densities than S. pistillata at the same treatment. Bleaching temperature threshold was 33°C or less for the two species S. pistillata and A. humilis where 51% of their zooxanthellae were lost after 24 h of exposure. In samples exposed to sediment concentration of 0.1 mg/cm2/L, zooxanthellae densities of A. humilis and S. pistillata did not show any decrease after 1 day. However, after 1 days of exposure to 0.5 mg/cm2/L, zooxanthellae densities were significantly different from those of the controls. Increases in sediment concentration to 1 mg/cm2/L caused a decrease in zooxanthellae densities that vary greatly over time. Measurements of zooxanthellae densities of A. humilis and S. pistillata at this stage revealed a highly significant difference between exposed and control sample. At 1 g/cm2/L, the number of zooxanthellae lost from A. humilis was higher than those lost from S. pistillata at same time. It is suggested that, the normal sedimentation rate for A. humilis and S. pistillata to be in an order of 1 mg/cm2/L or less.